PEMBANGUNAN APLIKASI SISTEM HUMAN RESOURCE UNTUK MANAJEMEN KARYAWAN DAN PROYEK DI CV. AVATAR SOLUTION - I Made Ari Madya Santosa; I Gusti Ngurah Anom Cahyadi Putra; Made Agung Raharja (Jurnal Pengabdian Informatika, 2025)
In an increasingly advanced era, organizations need to enhance employee performance to achieve optimal productivity. Job satisfaction and employee commitment are key factors in reaching these goals. This article proposes a web-based human resource management system application to improve employee productivity and satisfaction. This application allows employees to manage personal information and monitor performance transparently, helping to create a harmonious and productive work environment. With this implementation, it is expected to achieve improved organizational performance, higher job satisfaction, and stronger employee commitment.